(untitled) (The Journal of Plant Protection Sciences, 2020)
Laboratory studies were made to compare the toxicity of botanical insecticides viz. Neem oil, Pongamia oil and Nicotine extract in different conc./combinations along with dimethoate and dichlorvos on four coccinellid bio-control agents (Micraspis crocea, Micraspis discolor, Brumus suturalis and Scymnus bourdilloni). All botanicals tested showed least mortality and was on par with unsprayed control. Dimethoate (0.1%) was highly toxic causing 100% mortality. Whereas, dichlorvos (0.1%) was least toxic in comparison to dimethoate. Botanical insecticides tested in different conc./combinations are compatible with natural enemies and may be incorporated in IPM in mulberry ecosystem.